Highly Fluorescent, Photostable, and Ultrasmall Silicon Drug Nanocarriers for Long‐Term Tumor Cell Tracking and In‐Vivo Cancer Therapy. (6th November 2014) - Ji, Xiaoyuan; Peng, Fei; Zhong, Yiling; Su, Yuanyuan; Jiang, Xiangxu; Song, Chongxi; Yang, Liu; Chu, Binbin; Lee, Shuit‐Tong; He, Yao
<x xml:space="preserve">Abstract</x> Silicon nanoparticle (SiNP) nanocarriers feature strong fluorescence, ultrasmall size, robust photostability, and tunable drug‐loading capacity. Using SiNP nanocarriers, the first example of long‐term cancer cell tracking is successfully demonstrated. Furthermore, in vivo experiments show that tumor‐bearing mice treated with SiNP nanocarriers survive over 20 d without observable tumor growth, demonstrating the high‐efficacy chemotherapy of the Si nanocarriers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>